(3OjhGf SHW GHf GdJYGhjPjs - (3GHf GdJYGhjPj , CHh GdaJM eMeO Hf YHjOGddg Hf YHO Gddg, GHf GdJYGhjPj,J (B583 (3g` s ((3eMeO Hf CMeO Hf YHOGddg GdHLdj s)
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG bUjOI geRjI efgG(B: (3CfJe aj GdOfjG gOGI haj GdBNQI def Vd SYjg TaYGA s
(3BNQgG (B:s
(3ef bUjOI hbO CgOi gOjI Edi CHj Ydj Hf Gdhcjd UGMH GdOjhGf jSCdg bHhdgG(B: (3dG HQMJ QHYc GdJgGfj hQHY CYOGFc GdZQHGfG s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B278s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B115 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B764s
Keywords: (3GdCOHs